Two Cellobiohydrolase-Encoding Genes from Aspergillus niger Require d-Xylose and the Xylanolytic Transcriptional Activator XlnR for Their Expression - Gielkens, Marco M. C. (American Society for Microbiology, 1999)
Two cellobiohydrolase-encoding genes, cbhA and cbhB, have been isolated from the filamentous fungus Aspergillus niger. The deduced amino acid sequence shows that CbhB has a modular structure consisting of a fungus-type cellulose-binding domain (CBD) and a catalytic domain separated by a Pro/Ser/Thr-rich linker peptide. CbhA consists only of a catalytic domain and lacks a CBD and linker peptide. Both proteins are homologous to fungal cellobiohydrolases in family 7 of the glycosyl hydrolases. Northern blot analysis showed that the transcription of the cbhA and cbhB genes is induced by d-xylose but not by sophorose and, in addition, requires the xylanolytic transcriptional activator XlnR.